Remembering, Writing, and Women's Agency in Postcolonial Contexts: An Analysis of Embroideries by Marjane Satrapi - Rahmasari, Rifka Alif; Priyatna , Aquarini; Adipurwawidjana, Ari Jogaiswara (Journal of Language and Literature Studies, 2026)
In contemporary discussions of Iranian women’s writing, Embroideries (2005) by Marjane Satrapi is often read primarily as a humorous or subversive critique of patriarchy. However, less attention has been given to how the memoir constructs memory as a performative and collective site of agency within postcolonial feminist discourse. Set during an afternoon domestic gathering, the graphic narrative depicts Iranian women negotiating identity, sexuality, and honor through storytelling across three generations. Drawing on feminist narratology and postcolonial feminist theory, this study examines how narrative voice, dialogic exchange, and graphic sequencing work together to produce agency as a relational process rather than an individual attribute. Butler’s theory of performativity is applied to recurring speech acts such as gossip, confession, and teasing, showing how agency emerges through repetition, citation, and collective participation. Cixous’s concept of écriture féminine further illuminates how Satrapi’s fragmented visual style and intimate domestic dialogue transform everyday experience into a gendered mode of writing. Rather than presenting memory as passive recollection, the memoir figures remembering as an embodied and dialogic practice shaped by classed and domestic contexts. By displacing politics from spectacular historical rupture to intimate domestic interaction, the memoir reconceptualizes the collective as inherently political, demonstrating how shared storytelling operates as a mode of critique, negotiation, and survival. These findings contribute to feminist and postcolonial scholarship by expanding approaches to graphic memoir beyond trauma and autobiography, and by rethinking Iranian women’s agency as relational, performative, and grounded in everyday social practice.